2020
DOI: 10.2196/20836
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Experience of Cancer Pain From the Perspective of Patients and Family Caregivers to Inform Design of an In-Home Smart Health System: Multimethod Approach

Abstract: Background Inadequately managed pain is a serious problem for patients with cancer and those who care for them. Smart health systems can help with remote symptom monitoring and management, but they must be designed with meaningful end-user input. Objective This study aims to understand the experience of managing cancer pain at home from the perspective of both patients and family caregivers to inform design of the Behavioral and Environmental Sensing an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 71 publications
(75 reference statements)
0
7
0
Order By: Relevance
“…The specifics of these design processes vary, but typically involve end-user surveys and interviews combined with beta-testing. We found structured interviews with patients and caregivers, combined with input from clinical partners, essential in validating the design features of system components, as well as confirming which variables to measure with BESI-C ( 24 ) . Additionally, because nurses are particularly attuned to the patient experience, they can offer important insights into features of RHM systems that may be unnecessary, unduly burdensome, or simply inappropriate.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…The specifics of these design processes vary, but typically involve end-user surveys and interviews combined with beta-testing. We found structured interviews with patients and caregivers, combined with input from clinical partners, essential in validating the design features of system components, as well as confirming which variables to measure with BESI-C ( 24 ) . Additionally, because nurses are particularly attuned to the patient experience, they can offer important insights into features of RHM systems that may be unnecessary, unduly burdensome, or simply inappropriate.…”
Section: Discussionmentioning
confidence: 78%
“…It is also not intended to be a technical summary regarding specific computing and engineering aspects of RHM (although many such excellent articles exist [ 5 , 23 )). When applicable, examples are provided from my research with the Behavioral and Environmental Sensing and Intervention for Cancer (BESI-C) ( 15 , 24 ) RHM system. Because of the reality that within each challenge lie opportunities, and within each opportunity lie related challenges, each topic is presented with a discussion of both related challenges and opportunities and instances of where these intersect.…”
Section: Discussionmentioning
confidence: 99%
“…No other disease groups have been previously examined. While cancer and musculoskeletal chronic pain populations share similar symptoms in pain, there are marked differences around health beliefs to movement, [51][52][53] disease progression, 53,54 prognosis 55 and fatigue. 53 Psychologically, while both populations may present with depression and anxiety, the basis of these in relation to ongoing healthcare status may differ.…”
Section: Discussionmentioning
confidence: 99%
“…In those with cancer-related pain, caregivers frequently experience high levels of emotional distress as they support individuals who they are close to and who are at the end of their lives, often with unplanned health care utilisation or emergency department visits which can increase stress and anxiety. 54,55 Through these differences between cancer and non-cancer associated pain management, further study is warranted to explore the role of caregiver interventions for people with musculoskeletal diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Our research has a particular focus on supporting the pain management needs of patients with advanced cancer and their family caregivers in rural settings, a population with well-documented disparities and challenges related to symptom management [24][25][26][27]. The overall research protocol [28] and user-centered design process [29] for BESI-C have been reported in detail elsewhere. Briefly, BESI-C is an end-to-end sensing system that consists of (1) physical components (smart watches, environmental sensors, and localization beacons) deployed in patient homes to gather physiological, behavioral, and contextual data regarding pain events from the perspective of both patients and family caregivers and (2) an approach for data analytics (Figure 1).…”
Section: Objectivesmentioning
confidence: 99%